2015
DOI: 10.1007/s10854-015-3351-2
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation behaviour of ethylene-vinyl acetate–exfoliated graphene nanoplatelets (xGnP) composites

Abstract: The dielectric relaxation behaviour of the composites prepared by solution casting of exfoliated graphene nanoplatelets (xGnP) and ethylene vinyl acetate (EVA) were investigated. The percolation threshold was achieved at 17 phr (parts per hundred rubber) of xGnP loading. Filler contributions to the electrical property were observed by the increase in ac conductivity and permittivity in the composites. The effect of filler loading on the complex and real parts of the impedance were investigated. The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The EVA/reduced graphene oxide composites prepared by in situ polymerization showed an electrical conductivity of 2.7 ×10 -3 S/cm upon the addition of 6 wt % of the filler [43]. The electric percolation threshold of EVA composite prepared by solvent-casting was reported at a loading or 17 per hundred [44].…”
Section: Introductionmentioning
confidence: 97%
“…The EVA/reduced graphene oxide composites prepared by in situ polymerization showed an electrical conductivity of 2.7 ×10 -3 S/cm upon the addition of 6 wt % of the filler [43]. The electric percolation threshold of EVA composite prepared by solvent-casting was reported at a loading or 17 per hundred [44].…”
Section: Introductionmentioning
confidence: 97%
“…[ 46 ] However, as the frequency increases, the electric field changes rapidly and the period is very short, which makes the dipole's steering movement unable to keep up with the change of the electric field due to internal resistance. [ 68 ] At the same time, due to the increase in thickness, PANI forms a conductive path. When the thickness increases more than 75 µm, a leakage current phenomenon occurs due to the formation of a conductive path.…”
Section: Resultsmentioning
confidence: 99%
“…(2) When the frequency increases, the reversion of dipoles is unable to keep up with the change of electrical fields on account of resistance in the materials, which consequently forms relaxation. 47 (3) While the frequency reaches very high, some dipoles cease reversing that results in making no contribution to the permittivity. Observing Figure 6a,b, it is easily found that the permittivity of 2.83 vol % HBSiPA−TrGO/AR at 10 2 or 10 3 Hz is as high as 355 and 325, approximately 3.5 and 2.8 times that of 1.69 vol % TrGO/AR, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a comparison, the dielectric constant decreases in pace with frequency increasing with the addition of fillers, which is ascribed to the following explanations: (1) The dielectric constant of materials is caused by polarization; the polarization is originated from the directional alignment of some dipoles, which is capable of reversing the applied field with the electrical field due to the change of frequency. (2) When the frequency increases, the reversion of dipoles is unable to keep up with the change of electrical fields on account of resistance in the materials, which consequently forms relaxation . (3) While the frequency reaches very high, some dipoles cease reversing that results in making no contribution to the permittivity.…”
Section: Results and Discussionmentioning
confidence: 99%